PENGEMBANGAN KONTRAK PEMBELAJARAN EKONOMI MENGGUNAKAN WHIMSICAL - Setiawan, David Firna; Wahyuhastuti, Novika; Darmaputra, Mochamad Fadjar (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Learning contracts are generally used to achieve the goal, namely the professional competence of prospective workers. Therefore, learning contracts are not commonly used at the secondary education level. In fact, the learning contract is considered to have a positive impact in the process of increasing professional competence. This study aims to develop a learning contract using the Whimsical application. The learning contract was developed using the ADDIE model. The content and learning objectives are based on the standard content of the economic content of the secondary education level based on the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 21 of 2016 concerning the Content Standards of Primary and Secondary Education. The results of the study are expected to assist teachers in developing learning contracts that can be used by teachers of economics subjects. The results of this study are expected to have a positive impact on student learning outcomes. The process of developing an economic learning contract adopting the ADDIE mode includes five steps, namely, (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The results of the study show that the overall economic learning contract is categorized as very feasible both from the aspect of the quality of the content and objectives as well as the quality aspect of the learning contract both visualization and physical use.Keywords: Learning Contract; Economic course; Whimsicle